2018
DOI: 10.3390/ijerph15040694
|View full text |Cite
|
Sign up to set email alerts
|

Radon Levels in Indoor Environments of the University Hospital in Bari-Apulia Region Southern Italy

Abstract: Since 1988, the International Agency for Research on Cancer (IARC) has classified radon among the compounds for which there is scientific evidence of carcinogenicity for humans (group 1). The World Health Organization (WHO) recommends a reference radon level between 100 and 300 Bq/m3 for homes. The objective of this study is to measure the radon concentrations in 401 workplaces, different from the patient rooms, in 28 different buildings of the university hospital in Bari (Apulia region, Southern Italy) to eva… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
13
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 27 publications
(18 citation statements)
references
References 18 publications
(20 reference statements)
2
13
0
Order By: Relevance
“…Housing characteristics, such as floors, sump holes, ventilation, and heating systems were suspected for high indoor radon levels and health consequences [ 21 ]. A recent survey on radon levels in indoor environments of the university hospital in Bari reported an average concentration of radon lower than the WHO reference level (100 Bq/m 3 ) [ 22 ]. A radon survey conducted in 2013–2014 in various dwellings of Peninsula Salentina of the Apulia region, in Southern Italy, found that higher radon concentrations were found in bedrooms than in living rooms, underground, and at ground level rather than upper floors.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Housing characteristics, such as floors, sump holes, ventilation, and heating systems were suspected for high indoor radon levels and health consequences [ 21 ]. A recent survey on radon levels in indoor environments of the university hospital in Bari reported an average concentration of radon lower than the WHO reference level (100 Bq/m 3 ) [ 22 ]. A radon survey conducted in 2013–2014 in various dwellings of Peninsula Salentina of the Apulia region, in Southern Italy, found that higher radon concentrations were found in bedrooms than in living rooms, underground, and at ground level rather than upper floors.…”
Section: Discussionmentioning
confidence: 99%
“…Certainly, the study presents the limits of an observational study regarding the current data. Because of the small number of observations and lack of analytical data—for example, on the ventilation and air change rate for each building test and type of flooring [ 22 ]. Thus, these estimates need further validation to avoid bias.…”
Section: Discussionmentioning
confidence: 99%
“…All these agents are also classified in "Group 1" by the IARC, and the Italian National Institute for Insurance against Accidents at Work (INAIL) remunerates cases of NMSC caused by these substances. Furthermore, theoretical models supported by recent studies suggest that other new potential factors (i.e., radon, air pollution) may contribute to risk of skin cancer [16][17][18][19]. Several authors found an association between professional sun exposure and the risk of developing NMSC [2,[20][21][22][23]; furthermore, a higher rate of skin cancer (in particular, BCC and SCC) was detected in engineers, bricklayers, farmers, lifeguards, mountain guides, and mail carriers [2,4,[23][24][25][26][27][28][29].…”
Section: Introductionmentioning
confidence: 98%
“…In most countries there are predictive maps of radon content, mainly representing the igneous composition of the soil [ 19 , 20 , 21 , 22 ] For example, Sweden has developed maps based on the measurement of the geogenic potential of radon, which indicate the risk level by zone, estimated from the concentration of radon in the ground at 1 m depth [ 23 , 24 , 25 ]. Likewise, the usefulness of methods based on other variables, such as soil radio-226 concentration or uranium equivalent has also been tested.…”
Section: Introductionmentioning
confidence: 99%
“…Different aspects of the shelter have been studied: the constructive typology of the underground building, its historical context and the presence of radon on the inside obtained through rigorous measurement techniques. By virtue of the results obtained from the measurements, the shelter serves as a paradigm to demonstrate the relevant presence of more than 100 Bq/m of radon in the interior of an underground building in non-granitic soil [ 22 ].…”
Section: Introductionmentioning
confidence: 99%